Trade Union Membership in Eastern and Western Germany: Convergence or Divergence? - Claus Schnabel; Joachim Wagner (Institute for the Study of Labor (IZA), 2003)
An empirical analysis of various waves of the ALLBUS social survey shows that the level and the structure of unionization has become more and more similar in eastern and western Germany in the period 1992 to 2000. The originally high level of union density in eastern Germany has dropped below that of western Germany, and union membership has been falling steadily in both parts of the country since 1992. Repeated cross-sectional analyses indicate that the factors influencing individuals? probability of union membership have converged over time between western and eastern Germany. After an assimilation period of about ten years the same set of variables can be used to explain unionization in post-socialist eastern Germany and in traditionally capitalist western Germany.
Keywords: J51; 330; trade union membership; Germany; micro data; Gewerkschaftlicher Organisationsgrad; Neue Bundesländer; Alte Bundesländer; Deutschland